Employee Acceptance Decision Support System with AHP Method - Margaretha Ajeng Purbo Resmi (Institute of Computer Science, 2020)
The process of hiring Kanisius Printing Publisher Yogyakarta is the process of getting the best prospective employees from all existing applicants. In the process, applicants must go through several stages of selection, namely administrative tests, written tests, interview tests and medical tests. However, all processes are still done manually. This resulted in the recruitment process takes a long time in determining qualified applicants and in accordance with company criteria. In this research, a software decision-making support system for recruitment of employees is created which functions to help the company make the right decisions in a relatively faster time using the Analytical Hierarchy Process (AHP) method. The AHP method is a superior method for selecting competitive activities or many alternatives based on certain criteria. The main function of this software is to help the company, in this case the HRD section, to get prospective employees who match the criteria needed by the company. This software is implemented using the PHP MySQL programming language.